METABOLISM OF RESISTANT MUTANTS OF STREPTOCOCCUS FAECALIS IV. : Use of a Biophotometer in Growth-Curve Studies - Coultas, M. Katharine (1962)
Coultas, M. Katharine (Sloan-Kettering Institute for Cancer Research, Rye, N.Y.) and Dorris J. Hutchison. Metabolism of resistant mutants of Streptococcus faecalis. IV. Use of a biophotometer in growth-curve studies. J. Bacteriol. 84:393–401. 1962. — Analysis of data obtained using the Bonet-Maury and Jouan biophotometer has shown it to be an accurate, automatic device for recording an entire bacterial growth curve, from which quantitative measurements of growth rate can be calculated. Growth rate values obtained in this manner agree with those obtained by conventional methods. The instrument is described in detail and reference is given to other uses of this type of photometer. The growth curves of Streptococcus faecalis ATCC 8043 and three mutants resistant to purine analogues were compared in media with and without a purine. Differences in these growth curves were evident. In the purine-deficient medium SF/AZAG, the 8-azaguanine-resistant mutant had the shortest doubling time, 61 min, followed by the two 6-mercaptopurine-resistant mutants (SF/MPcc, 72 min; SF/MP, 91 min), and finally the wild strain with a doubling time of 135 min. In the medium supplemented with xanthine, the respective doubling times were 52, 61, 68, and 68 min.